Descriptive Study on Teaching Reading at The EighthGrade of SMP Muhammadiyah 4 Surakartain 2015/ 2016 Academic Year - Munika, Dwi Oktavia; , Drs. Djoko Srijono, M.Hum; , Aryati Prasetyarini,S.Pd,. M.Pd (2016)
This reserach paper is intended to describe teaching reading to the eighth grade students of SMP Muhammadiyah 4 Surakarta in 2015/2016 Academic Year. The purpose of this research is to know the methods for teaching reading used by the teacher at the eighth grade of SMPMuhammadiyah 4 Surakarta in 2015/2016 Academic Year. This research is a descriptive qualitative research. The writer collects the data by observing the English class and conducting interview with the teacher. The data are taken from all elements of teaching reading committed by the teacher and the students and other sources such as field note, syllabus, textbook, and lesson plan.The methodofcollectingdata are observation, interview, and document analysis. From the research finding and discussion, the writer draws the following conclusion.First, the methods used by the teacher in teaching reading at the eighth grade of SMP Muhammadiyah 4 Surakarta in 2015/2016 Academic Year are Grammar Translation Method (GTM), Direct Method (DM), and Cognitive Code Language (CCL). Second, the problems faced by the teacher are: (1) limited vocabulary of the students, (2) uncontrolled class situation, and (3) limited media used. Third, the writer gives some suggestions as follows: (1) to the teacher: the teacher should use the media for teaching optimally and is expected to apply more creative methods so that the students are not bored.The teacher should use her affirmation to keep control the situation in the class in order to create the comfort environment to learn together, and the teacher must increase the intensity in communication with the students using English; (2) to the student: the students must pay attention during the teaching-learning process so they can accept the material given, the students should improve their vocabulary by practicing translation on the text given, memorizing the words in the dictionary, and the students must practice English more in daily activity in order to be a habit especially in reading. Keywords: descriptive study, teaching reading